Penguatan Nilai-Nilai Moderasi Beragama Dalam Majelis Taklim di Kota Panyabungan - Siregar, Irma Suryani; Rohman, Rohman (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
Religious moderation is an important agenda for every country in building peaceful relations between religious communities. As one of the fundamental values ​​in religion, strengthening religious moderation is a pure movement that aims to form moderate attitudes in society. This study aims to explore the strengthening of the values ​​of religious moderation preached by religious teachers to the community. Data collection methods are carried out by observation, interviews, documentation, and focus group discussions. Data collection focuses on the social situation that exists in the taklim assembly (place), ustaz/jemaah (actors), and the study process (activity) which interacts synergistically. Data were analyzed inductively through data reduction, data presentation, data classification, analysis, and conclusion. The results of the study show that the taklim assembly is an effective forum for instilling the values ​​of religious moderation in the community. The determination of moderate ustaz is an important factor in instilling an attitude of moderation in the community. Ustaz strengthened religious moderation by explaining Islamic teachings that were friendly to all groups. Islamic teachings in every field of study are preached by emphasizing the formation of humble, humanist, friendly, and obedient attitudes in carrying out religion. The values ​​of moderation in the studies presented in general have come into contact with the values ​​of balance, acceptance of local culture, tolerance, and anti-violence, and a commitment to togetherness among citizens.